17‐4: Evaluate and Upgrade Picture Quality of Local Dimming Mini‐LED LCD. Issue 1 (25th September 2020) - Chen, Chun-Chi; Qiu, Young-Yuan; Zheng, Wei-Wei; Gang, Yu; Chiu, Chung-Yi; Zhao, Bin; Zhang, Xin
Abstract : Picture quality can be improved by mini‐LED backlight, but it will case halo issue, so we need a simulation tool to check the picture quality, then we can fine tune the parameter of design for better picture quality. In this paper we develop a system to simulate the picture quality of mini LED backlight LCD and analyze the halo issue. We simulated LC optics by LCD master, then we evaluated the optical performance of mini‐LED backlight with local dimming function by Matlab, and last we simulated the picture gotten by human eye in different the distance and angle of viewer. Through this system we can simulate the picture quality of mini‐LED backlight, and we can fine tune the parameter of design for making the picture quality better.